Full-Endoscopic Transforaminal Ventral Decompression for Symptomatic Thoracic Disc Herniation with or without Calcification: Technical Notes and Case Series - Shangju Gao; Jingchao Wei; Wenyi Li; Long Zhang; Can Cao; Jinshuai Zhai; Bo Gao (Pain Research and Management)
Background. Symptomatic thoracic disc herniation is a challenge in spinal surgery, especially for cases with calcification. Traditional open operation has a high complication rate. The authors introduced a modified full-endoscopic transforaminal ventral decompression technique in this study and evaluated its imaging and clinical outcomes. Materials and Methods. Eleven patients with symptomatic thoracic disc herniation who underwent full-endoscopic transforaminal ventral decompression in a single medical center were enrolled. The surgical technique was performed as described in detail. Dilator sliding punching, endoscope-monitored foraminoplasty, and base cutting through the “safe triangle zone” are the key points of the technique. Clinical outcomes were assessed by the modified Japanese Orthopedic Association (mJOA) score for neurological improvement and the visual analogy score (VAS) for thoracic and leg pain. The operation time, hospital stay, and complications were also analyzed. Results. Postoperative magnetic resonance imaging (MRI) revealed good decompression of the spinal cord. The mJOA improved from 7.4 (range: 5–10) to 10.2 (range: 9–11). Axial thoracic pain improved in 8 of 9 patients. Leg pain and thoracic radicular pain improved in all patients. No complications were observed. The average operation time was 136 minutes (range: 70–180 minutes). The average length of hospital stay was 5.3 days (range: 2–8 days). Conclusion. Minimally invasive full-endoscopic transforaminal ventral decompression for the treatment of symptomatic thoracic disc herniation with or without calcification is feasible and may be another option for this challenging spine disease.